Intracranial Pressure and Cerebral Hemodynamic Monitoring After Cardiac Arrest in Pediatric Pigs Using Contrast Ultrasound‐Derived Parameters. (15th September 2021) - Shin, Samuel S.; Sridharan, Anush; Khaw, Kristina; Hallowell, Thomas; Morgan, Ryan W.; Kilbaugh, Todd J.; Hwang, Misun
Abstract : Objectives: We explore the correlation of contrast‐enhanced ultrasound (CEUS) parameters to intracranial pressure (ICP) in a porcine experimental model of pediatric cardiac arrest. Methods: Eleven pediatric pigs underwent electrically induced cardiac arrest followed by cardiopulmonary resuscitation. ICP was measured using intracranial bolt monitor and CEUS was monitored through a cranial window. Various CEUS parameters were monitored at baseline, immediately post return of spontaneous circulation (ROSC), 1 hour‐post ROSC, and 3 hours post‐ROSC. Results: There was significant ICP correlation with wash‐out slope assessed by CEUS time intensity curve analysis at immediate post‐ROSC. At 3 hours post‐ROSC there was also significant negative correlation between ICP and peak enhancement which may be due to the evolution of anoxic injury. Conclusion: The use of CEUS in assessing disruption of cerebral hemodynamics and ICP post cardiac arrest will need future validation and comparison to other imaging modalities. The correlation between CEUS parameters and ICP may be due to the alterations in cerebral autoregulation that result from anoxic brain injury.